Unveiling Misconceptions in Chemistry: A Review of Causes, Common Patterns, and Levels of Student Understanding - Munawwarah Munawwarah; Ayu Ashari (Universitas Cokroaminoto Palopo, 2025)
The urgency of addressing this issue lies in its long-term impact on students’ conceptual development, from secondary school to pre-service teachers. Misconceptions remain a critical issue in chemistry education because they obstruct students’ ability to integrate macroscopic, submicroscopic, and symbolic representations, thereby limiting scientific literacy and problem-solving skills.. This review aims to identify chemistry topics most prone to misconceptions, analyze recurring misconception patterns, examine their underlying causes, and assess the reported levels of misunderstanding. A systematic literature review was conducted using the PRISMA 2020 framework, with inclusion criteria focusing on empirical studies published between 2015 and 2025 that employed diagnostic instruments (two-tier, three-tier, four-tier, five-tier, or CRI) and reported data on misconceptions. From an initial 100 records, 30 studies met the criteria and were analyzed. The synthesis shows that the highest average misconception rates occur in buffer solutions, hydrolysis, chemical bonding, and electrolytes (often exceeding 50%), while equilibrium, stoichiometry, thermochemistry, and redox reactions display moderate to lower levels. Common patterns include viewing all hydrogen-containing compounds as acids, assuming ionic bonds form between molecules, perceiving stoichiometry as purely algorithmic, and believing buffer solutions neutralize acids and bases completely. The findings reveal that misconceptions are driven by a combination of prior knowledge, the abstract nature of chemistry, inaccurate textbooks, insufficient teacher explanations, and ambiguous chemical language. The review concludes that misconceptions in chemistry are systematic and persistent, underscoring the need for diagnostic assessments and pedagogical strategies that integrate multiple representations and targeted corrective interventions.